A rotating bioreactor for the production of biofilms at the solid–air interface. Issue 3 (6th January 2022) - Kretschmer, Martin; Hayta, Elif N.; Ertelt, Marvin J.; Würbser, Michaela A.; Boekhoven, Job; Lieleg, Oliver
Abstract: Conventional bioreactors are typically developed for the production of planktonic bacteria or submerged biofilms. In contrast, reactors for the continuous production of biofilms at the solid–air interface are scarce, and they require specific conditions since the bacteria need to attach firmly to the surface and require a permanent supply of moisture and nutrients from below. Recently, research from the field of civil engineering has pinpointed an increased need for the production of terrestrial biofilms: several variants of Bacillus subtilis biofilms have been shown to be useful additives to mortar that increase the water repellency, and, thus, the lifetime of the cementitious material. The bioreactor introduced here allows for the continuous production of such bacterial biofilms at the solid‐air interface, and they have virtually identical properties as biofilms cultivated via classical microbiological techniques. This is made possible by equipping a rotating cylinder with a porous membrane that acts as a solid growth substrate the bacterial biomass can form on. In this configuration, nutrient supply is enabled via diffusive transport of a suitable growth medium from the core volume of the cylindrical reactor to the membrane surface. In addition to cultivating bacterial biofilms, the versatile and adaptable set up introduced here also enables the growth of other microbial organisms including the yeast Saccharomyces cerevisiae and the fungus Penicillium chrysogenum . Abstract : The authors present a novel bioreactor for the production of biofilms from the bacterial species Bacillus subtilis and other microbial organisms, such as the yeast Saccharomyces cerevisiae and the fungus Penicillium chrysogenum . The bioreactor is based on a rotating cylinder and allows continuous biofilm production at the solid–air interface. Furthermore, it is demonstrated that B. subtilis natto biofilm produced with this bioreactor is suitable as an additive to increase the hydrophobicity of mortar.